(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article discusses the issues of speech development, development of thinking, the formation of mathematical concepts in the education of preschool children through the organization and family cooperation, as well as methods of teaching children in the family, knowledge-strengthening games illuminated.